PERSELINGKUHAN DAN PERCERAIAN (SUATU KAJIAN PERSEPSI WANITA) ADULTERY AND DIVORCE (STUDY OF WOMAN PERCEPTION) - Eka Nilakusmawati, Desak Putu; Srinadi, I Gusti Ayu Made (Jurnal Studi Jender SRIKANDI; Vol. 6, No. 2 Juli 2007, 2012)
Harmony and eternity of marriage become marriage expectancy for every married couples. Nevertheless, few of marriaged ended up broken because one of them do adultery. The result of research used purposive sampling and survey method approach of 50 respondents in Denpasar showed that most of respondents agree about adulterous have consequence concerning The God in the form of sadness and feel sin that God will ever forgive his/her and feel guilty continuously towards his/herself, their children, their spouse, family and work places. Indeed, this matter basically more related with moral consequences for the adulterous. Research showed that dominan factor of adultery are less communication between couples (22%); economic factor (16%); less care of the spouse specially for psychological needed (20%); one of spouse more dominant than other (8%) and the other factors (34%). Total respondent have perception that adultery impact to loose of home peace. Explanation about in which way adultery have consequences to loose of home peace, showed 74% respondent percepted cause of no more harmony at home; less trust and respect of the family members and spouse (12%); less care to family (8%) and because of distrust to the spouse (4%). Respondent perception about the follow-up of adultery showed that more than 50% respondent agree to forgive his/her spouse and most of them not agree to divorce and do same thing too (adultery). That?s because the negative impact of divorce to the children which is mostly negative likely : emotional development problem, profound grieving and irrational fears and as a cumulative experience for the children. Most of respondent not agree to stick divorce as the choice to follow up the adultery and indicated to choose to forgive their spouse.
Keywords: SELINGKUH